Ethnic Drag : Performing Race, Nation, Sexuality in West Germany - Sieg, Katrin, 1961- (Book collections on Project MUSE., 2002)
"The Holocaust is considered a singularly atrocious event in human history, and many people have studied its causes. Yet few questions have been asked about the ways in which West Germans have "forgotten," unlearned, or reconstructed the racial beliefs at the core of the Nazi state in order to build a democratic society. This study looks at ethnic drag as one particular kind of performance that reveals how postwar Germans lived, disavowed, and contested "Germanness" in its complex racial, national, and sexual dimensions. Using engaging case studies, Ethnic Drag traces the classical and travestied traditions of Jewish impersonation from the eighteenth century onward to construct a pre-history of postwar ethnic drag. It examines how shortly after World War II mass culture and popular practices facilitated the repression and refashioning of Nazi racial precepts. During a time when American occupation authorities insisted on remembrance and redress for the Holocaust, the Wild West emerged as a displaced theater of the racial imagination, where the roles of victim, avenger, and perpetrator of genocide were reassigned"--Publisher's description